Case report: Mitochondrial trifunctional protein deficiency caused by HADHB gene mutation (c.1175C>T) characterized by higher brain dysfunction followed by neuropathy, presented gadolinium enhancement on brain imaging in an adult patient - Ishikawa, Ruoyi; Nakamori, Masahiro; Takenaka, Megumi; Aoki, Shiro; Yamazaki, Yu; Hashiguchi, Akihiro; Takashima, Hiroshi; Maruyama, Hirofumi (Frontiers in Neurology, 2023)
Mitochondrial trifunctional protein (MTP) deficiency is an autosomal recessive disorder caused by impaired metabolism of long-chain fatty acids (LCFAs). Childhood and late-onset MTP deficiency is characterized by myopathy/rhabdomyolysis and peripheral neuropathy; however, the features are unclear. A 44-year-old woman was clinically diagnosed with Charcot-Marie-Tooth disease at 3 years of age due to gait disturbance. Her activity and voluntary speech gradually decreased in her 40s. Cognitive function was evaluated and brain imaging tests were performed. The Mini-Mental State Examination and frontal assessment battery scores were 25/30 and 10/18, respectively, suggesting higher brain dysfunction. Peripheral nerve conduction studies revealed axonal impairments. Brain computed tomography showed significant calcification. Magnetic resonance imaging revealed an increased gadolinium contrast-enhanced signal in the white matter, suggesting demyelination of the central nervous system (CNS) due to LCFAs. The diagnosis of MTP deficiency was confirmed through genetic examination. Administration of L-carnitine and a medium-chain fatty triglyceride diet was initiated, and the progression of higher brain dysfunction was retarded within 1 year. This patient's presentation was suggestive of CNS demyelination. The presence of brain calcification, higher brain dysfunction, or gadolinium enhancement in the white matter in patients with peripheral neuropathy may be suggestive of MTP deficiency.